Perioperative outcomes of neoadjuvant chemotherapy plus camrelizumab versus neoadjuvant chemotherapy plus tislelizumab for locally advanced esophageal squamous cell cancer: a real-world retrospective study - Zhao, Qi; Yuan, Yusen; Xu, Tongxin; Yan, Ningning; Li, Fei; Lu, Juntao; He, Ming; Yan, Zhaoyang (Frontiers in Immunology, 2025)
BackgroundWhile neoadjuvant chemoimmunotherapy shows promise for locally advanced esophageal squamous cell carcinoma (ESCC), optimal regimen selection remains challenging. This study compares perioperative outcomes between camrelizumab- and tislelizumab-based neoadjuvant chemoimmunotherapy in ESCC.MethodsWe conducted a retrospective analysis of 209 clinical stage II-IVA ESCC patients treated at Hebei Medical University Fourth Hospital (October 2020-December 2023) who underwent neoadjuvant chemoimmunotherapy (camrelizumab, n=119; tislelizumab, n=90) followed by esophagectomy.ResultsComparable pathological responses were observed between groups: pathological complete response (31.1% vs 30.3%, P=1.00), major pathological response (44.4% vs 42.9%, P=0.89), and pathological downstaging (67.8% vs 73.9%, P=0.36). Perioperative complication rates, including hematologic toxicities, immune-related adverse events, and surgical complications, were similar (all P>0.05). The tislelizumab group demonstrated significantly lower unplanned ICU transfer rates (P=0.04), while operative parameters (duration, blood loss, R0 resection) showed no differences.ConclusionTislelizumab-based chemoimmunotherapy demonstrates comparable efficacy and safety to camrelizumab-based regimens, potentially representing a viable neoadjuvant option for locally advanced ESCC.